Effects of UV-B irradiation on poly(vinyl alcohol) and Ixora siamensis anthocyanins-coated glass - Mat Nor, N.A.; Aziz, N.; Adnan, A.F.M.; Taha, R.M.; Arof, Abdul Kariem (Emerald, 2013)
Purpose – The purpose of this paper is to evaluate the potential of natural colourants from fruits of Ixora siamensis for coating applications, to study its glossiness and effectiveness against UV-B irradiation. Design/methodology/approach – In this study, natural colourants from the fruits of Ixora siamensis were extracted using trifluoroacetic acid-methanol solution. Anthocyanins and organic acid variants were mixed together to form co-pigments. Different concentrations of ferulic and gallic acid co-pigments were added to a blended solution of poly (vinyl alcohol), PVA and anthocyanin (from Ixora siamensis) to form a coating system. The coatings were exposed to UV-B irradiation at room temperature in air using a UV-lamp which emitted radiation at 312 nm. The effects of UV-B irradiation on the coating system were evaluated using glossiness test and UV-visible spectroscopy. Findings – Anthocyanins are unstable and can quickly lose their colour. One of the methods of preserving the stability of these pigments is by co-pigmentation. Co-pigmentation of anthocyanin with organic acid variants resulted in an increase in both hyperchromic effects (DA) and bathochromic shifts (Dl). In this study, ferulic acids yielded better results compared to gallic acids. Research limitations/implications – Samples with co-pigmentation give better result compared to the untreated samples. The addition of 0.5 and 1.0 per cent ferulic acid improves the gloss properties and resistivity of the samples towards the UV irradiation. Thus, in order to study the effectiveness of ferulic acid as additive and improving the properties of the samples, the percentage of ferulic acid added and exposure time could be increased. Practical implications – The method developed provided a simple and efficient solution for improving the UV resistance of anthocyanin blend with poly (vinyl alcohol), PVA UV absorber. Effect of ferulic acid as UV absorber, if added in more concentration, can be further studied for optimization. Social implications – The social implication is the use of local plant species as a low cost source of natural pigments in coating system. Originality/value – The method for improving the resistance towards UV irradiation of anthocyanin blend with poly (vinyl alcohol), PVA was novel and could find numerous applications for natural product based on plant pigment.